Assistant laique de communauté: Repères pour un discernement ecclésiologique et canonique - Waymel, Dominique (Monitor ecclesiasticus, 2018)
Some apostolic religious congregations, faced with the ageing of their members, have to face the difficulty of finding a brother or sister to whom to entrust the exercise of authority in the so-called intermediary local communities. In this context of lack of members, the possibility of entrusting this service to a lay community assistant - a new legal figure of government - has arisen in the Church of France. This article seeks to give some giudelines for ecclesiological and canonical discernment by taking into account the evolution of the place of the laity in the lige and mission of the Church but also the specificity of the choice of life of the members of a religious institute. The contribution focuses, on the one hand, on the possibility of creating a new office while highlighting some points of attention. On the other hand, it questions the possibility of drawing inspiration from the treatment proposed by the canon Law in certain situations of shortage and in partivular that of lack of priests to carry out pastoral duties.